2020
DOI: 10.3390/su12103988
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Airport Capacity Efficiency by Selecting Optimal Aircraft and Airline Business Model

Abstract: This paper analyses the impact of airline business models on airport infrastructure and operational capacity and answers the question how to optimize capacity in order to achieve maximum efficiency and profitability as well as how to maintain an adequate level of service quality. As part of the research, a new model was created as an integral part of the Airport Management Strategy Software (AMSS) application. The purpose of the application is to enable the airport management to review and optimize operations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, there is no evidence that it has a farelowering effect. In addition, Secilmis and Koc (2016) [3] studied the relationship between air transport demand volume and economic variables influencing it in Turkey and the European Union: According to the findings, there are two effects on air demand: national capita income and the industrial production index have a positive influence, while airfares, inflation, and the exchange rate have an inverse influence. Furthermore, Schmalz et al (2017) [4] investigated the variables influencing European aviation demand in terms of both quantitative and qualitative data; the regression analysis revealed that the key variables of air demand are the country's GDP, education level, and geographical location.…”
Section: Development Of a Regression Model To Forecast Air Travel Dem...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no evidence that it has a farelowering effect. In addition, Secilmis and Koc (2016) [3] studied the relationship between air transport demand volume and economic variables influencing it in Turkey and the European Union: According to the findings, there are two effects on air demand: national capita income and the industrial production index have a positive influence, while airfares, inflation, and the exchange rate have an inverse influence. Furthermore, Schmalz et al (2017) [4] investigated the variables influencing European aviation demand in terms of both quantitative and qualitative data; the regression analysis revealed that the key variables of air demand are the country's GDP, education level, and geographical location.…”
Section: Development Of a Regression Model To Forecast Air Travel Dem...mentioning
confidence: 99%
“…As well as one that greatly contributes to global economic progress, political stability, and an increase in social values. The estimation of air travel demand is an important factor in air carrier and new line planning, as well as potential markets, strategic plans, and the financial sector [3]. Schmalz et al (2017) [4] studied variables impacting demand, including population, Gross Domestic Product (GDP), income, labor market, commerce, schedule, and airfares.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, Yoon and Jeong conducted an extensive analysis to estimate passenger delay using a discrete event simulation model, and they developed a plan to expand Te goal of this approach was to precisely determine the potential free capacity of an airport's infrastructure and operations, as well as the aircraft that can be added to increase and maximize the airport's efciency by maintaining an adequate level of service and conducting airport business without causing any delays [19]. However, recent studies have shown that agentbased models can be used as a proactive alternative in airport planning, operations, and commercialization strategies.…”
Section: Te Efect Of Conveyor Belt Speedmentioning
confidence: 99%
“…In addition, there is a need to focus on sustainability and environmental responsibility. Knowing the business model is one of the most important factors during any crisis, as it allows the owner to react flexibly to change and ensure the sustainable development of the airport [24][25][26].…”
Section: Introductionmentioning
confidence: 99%